Essentials of Mesenchymal Stem Cell Biology and Its Clinical Translation - Zhao, Robert Chunhua. (Springer Netherlands : Imprint: Springer, 2013)
Mesenchymal stem cells (MSCs), a type of adult stem cells, have attracted the attention of scientists and physicians alike due to their unique biological properties and potential for disease treatment. As stem cell research is complex and progressing rapidly, it is important that the experts in this field share their views and perspectives. This book, co-edited by leading global researchers, is divided intothree major sections and covers a broad range of topics concerning MSCs during their transition from benchside to bedside. The book is intended for researchers and clinicians in the field of stem cells. Dr. Robert Chunhua Zhao, a Cheung Kong Professor of Stem Cell Biology, is Professor of Cell Biology at the Institute of Basic Medical Sciences & School of Basic Medicine, Chinese Academy of Medical Sciences & Peking Union Medical College (PUMC), Beijing, China. He is Director of the Center for Tissue Engineering, PUMC and Chief Scientist of the National Basic Research Program of China (973 Program ). He also serves as Regional Editor of Stem Cells and Development.